2023
DOI: 10.1186/s12014-023-09419-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics analysis in different stages of urothelial bladder cancer for identification of potential biomarkers: highlighted role for antioxidant activity

Abstract: Background Non-muscle-invasive bladder cancer (NMIBC) has a high recurrence rate and muscle-invasive bladder cancer (MIBC) has unfavorable outcomes in urothelial bladder cancer (UBC) patients. Complex UBC-related protein biomarkers for outcome prediction may provide a more efficient management approach with an improved clinical outcome. The aim of this study is to recognize tumor-associated proteins, which are differentially expressed in different stages of UBC patients compared non-cancerous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…In this study, proteomic analysis of bladder cancer was completed by LC−MS, and 331 differential proteins were also reported to be differential proteins in other studies ( 16 20 , 23 34 ). The differentially expressed proteins reflected the functions of cell motility, proliferation, metabolism, necrosis and signal transduction.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this study, proteomic analysis of bladder cancer was completed by LC−MS, and 331 differential proteins were also reported to be differential proteins in other studies ( 16 20 , 23 34 ). The differentially expressed proteins reflected the functions of cell motility, proliferation, metabolism, necrosis and signal transduction.…”
Section: Discussionmentioning
confidence: 85%
“…In the latest study in 2023, Tabaei S et al. ( 20 ) collected urine protein information from 42 urine samples (25 nonmuscle invasive bladder cancer and 17 muscle invasive bladder cancer samples) by 2-DE and LC-MS, and 12 differential expressed proteins were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic pro ling of bladder cancer tissue performed by others revealed subtype and stage-related differences converging on glucolipid metabolism. [11][12][13] Whole-organ spatial geographic analyses revealed that bladder carcinogenesis may develop innocuously over several decades and can be divided into dormant and Highly variable mutagenesis signatures were identi ed in individual mucosal samples but signatures 1 and 6 were dominant. 14 Moreover, the development of α, β, and ϒ mutations were driven by distinct mutational mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, mass spectrometry (MS)-based proteomics has become a widely used platform for clinical biomarker discovery and studying cellular signaling networks. This has led to technological developments of fast sequencing mass spectrometers that facilitate short online liquid chromatography tandem mass spectrometry (LC-MS/MS) enabling highthroughput analyses of hundreds of samples per day (1)(2)(3)(4). It is increasingly feasible to utilize LC-MS/MS for analyzing large patient cohorts but the bottlenecks for large-scale studies have moved to the pre-and post-analytical sample processing steps, which are unable to keep up with the increased throughput of the LC-MS/MS analyses.…”
Section: Introductionmentioning
confidence: 99%